2008
DOI: 10.1007/s00401-008-0427-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased PrPC expression correlates with endoglin (CD105) positive microvessels in advanced carotid lesions

Abstract: Normal cellular prion protein (PrP(C)) has multiple functions but its role in the development of atherosclerosis has not been studied. Our pilot microarray data showed increased expression of PrP(C) in tissue samples of complicated carotid lesions. Therefore in this study, we aimed to investigate its localisation within atherosclerotic arteries and its concentration in patient plasma. PrP(C) expression was examined using an enzyme immunometric assay (EIA) in plasma from patients undergoing endarterectomy. Caro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Of note, the use of CD31 as a sole marker for EMP detection is controversial and has not been consistently shown to distinguish EMPs from PMPs. CD105 (endoglin) is a transmembrane glycoprotein found in the vast majority of the microvessels in atheroma and with a pronounced expression around the periphery of the lipid core [29]. Vascular cell adhesion molecule-1 (VCAM-1, CD106) is expressed on activated endothelial cells and participates in the inflammatory initiation and progression of atherosclerotic plaques [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the use of CD31 as a sole marker for EMP detection is controversial and has not been consistently shown to distinguish EMPs from PMPs. CD105 (endoglin) is a transmembrane glycoprotein found in the vast majority of the microvessels in atheroma and with a pronounced expression around the periphery of the lipid core [29]. Vascular cell adhesion molecule-1 (VCAM-1, CD106) is expressed on activated endothelial cells and participates in the inflammatory initiation and progression of atherosclerotic plaques [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…From a pathological point of view, the activation of the PrP C gene is increased in response to hypoxia that occurs during ischaemic events [119,203,204,205]. Furthermore, in vitro studies clearly indicate that PrP C plays a critical role in the vascular recovery of brain- and carotid-damaged regions [206,207]. …”
Section: Role Of Copper Transport Systems During Angiogenesismentioning
confidence: 99%
“…Also other studies showed higher expression of endoglin in atherosclerotic vessels when compared with non-diseased vessels, suggesting that endoglin participates in atherogenesis (Piao and Tokunaga, 2006;Tashiro et al, 2002). Additionally, endoglin expression was linked to neo-angiogenesis within atherosclerotic aortic and carotid plaques, supporting its role in this process (Krupinski et al, 2008). Moreover, endoglin serum levels were found to be elevated in patients with atherosclerosis and correlated with total cholesterol levels (Blann et al, 1996).…”
Section: Endoglin the Accessory Type III Receptormentioning
confidence: 82%